Effects of electric fields on protein unfolding and aggregation : Inﬂuence on edible films formation - Pereira, Ricardo (2010)
Electric fields application is receiving increased attention because of its uniform heating of liquids. The mechanisms of unfolding and aggregation of whey proteins during ohmic heating may influence properties of edible films made thereof. The aim of this work was to evaluate the effects of ohmic heating on physical and structural properties of whey protein edible films and compare them with those obtained by conventional heating. The results showed that ohmic heating determined less aggregation and lower concentration of free sulphydryls in film-forming solutions. Ohmic films were thinner, less permeable to water vapor and presented nearly the same mechanical properties of conventional films. Ohmic heating induced protein conformational changes by increasing the contents of -sheet structures in the film network. This work emphasized the effects of ohmic heating in unfolding and aggregation mechanisms of whey proteins during heat denaturation, which determined the production of protein edible films with distinctive properties.